Sustainability assessment to support governmental biodiesel policy in Colombia: A system dynamics model. (10th January 2017) - Espinoza, A.; Bautista, S.; Narváez, P.C.; Alfaro, M.; Camargo, M.
Abstract: Combustion of fossil fuels in the transport sector represents the second largest source of greenhouse gas emissions. For this reason, governments are fostering diversification of energy sources by creating a set of governmental environmental policies and initiatives. In this context, biofuels are expected to represent a substantial part of source diversification, but it is necessary to assess the sustainability of their market to explore its effect on economical, technological, social, political and environmental dimensions. This research presents a dynamic simulation modelling of the Colombian biodiesel market and analyzes the policy support instruments for creating and managing it. A system dynamics based model is proposed to enable decision-makers to understand the influences between the different variables that describe the system and the impact of the biodiesel government policy in Colombia. The primary focus of this paper is to establish the characteristics of each sustainability dimension for the case of study and apply the system dynamics methodology with different types of validation. Finally, the Colombian market status and a sensitivity analysis are developed. The results show that in order to support the development of this sector, it is necessary to diversify the raw materials for the production of biodiesel in the medium term, which means raw materials without competence for the primary rainforest or competition with food productive lands.